2013
DOI: 10.1007/s13280-013-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

Transboundary Socio-Ecological Effects of a Marine Protected Area in the Southwest Atlantic

Abstract: Marine Protected Areas (MPAs) have been regarded as an alternative to protect natural resources and to improve fisheries. However, MPAs may also have negative socio-economic consequences on fishing communities. We aimed to check the effectiveness of a socially conflicting MPA in Brazil by assessing target reef fish biomass in islands inside (n = 6) and outside (n = 6) the MPA, fisheries' productivity (biomass), catch per unit of effort (CPUE), and fishers' socioeconomic status (mainly fishers' income) in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…10), except for 2 studies with undetermined outcomes [47,48]. There were more reported studies of state regime performing similarly to open access [49][50][51][52][53] than community performing similarly to open access [54]. Moreover, Latin America saw more studies of state regimes reportedly performing similarly to open access regimes than Asia and Africa combined.…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
“…10), except for 2 studies with undetermined outcomes [47,48]. There were more reported studies of state regime performing similarly to open access [49][50][51][52][53] than community performing similarly to open access [54]. Moreover, Latin America saw more studies of state regimes reportedly performing similarly to open access regimes than Asia and Africa combined.…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
“…Both aspects are analyzed in the four articles of this section. Lopes et al (2013) examine the effectiveness of a socially conflictive MPA between stakeholders in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Defeo et al [13] addressed the importance of the social-ecological systems of small-scale fisheries considering the effects of climate change, markets and governance: for example, they concluded that weak governance, market globalization, fishing pressure and climate change contributed to resource depletion in shellfisheries of Latin America. Lopes et al [14] have shown that marine protected areas did not visibly protect either fisheries or fishermen in fisheries from Paraty, SE Brazil. Berkes [15] have pointed out that there is need to understand motivation to conserve and that benefits can include economic, cultural, social and political aspects.…”
Section: The Journal Of the Marine Science Research And Developmentmentioning
confidence: 99%